Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2004)
Table of Content Rebecca Warren – SHE by Greg Hilty 20 Years of Parkett Essay by Johanna Burton, Interview with Franz West Christian Marclay Christian Marclay’s Cochlear Implants by Philip Sherburne Wise Cracks by Ingrid Schaffner The Bride, revived by her bachelors by Philippe Vergne Wilhem Sasnal Painting Recording by Megan Dailey Sludge by Adam Szymczyk Petite sensation by Gregor Jansen Gilian Wearing I’m Desperate by Dan Cameron The Encounter with Reality by Gordon Burn Gillian Wearing on her ALBUM series – interview by Cay Sophie Rabinowitz Nic Hess, Insert Choreography of Chaos – Aernout Mik by Dominic van den Boogerd Horror Vacui, The Subject as Image in Mark Lecky’s Parade, Les Infos du Paradis by Catherine Wood Joan Jonas, Cumulus from America by Carolee Thea Hybridity, Eros, and Death, Cumulus from Europe by Gabriele Schor A Whole Life in One Minute by Tineke Reijnders
﻿Our core objective, since we first started 20 years ago, has been to work closely with contemporary artists, for we consider them partners in a joint venture. They, in turn, have consistently demonstrated their commitment in collaborations that contribute substantially to the renown of Parkett. For the 70 volumes published over the past 20 years, our artists have designed and created 150 editions and 62 inserts. An international roster of eminent writers has played an equally substantial role in defining the character of Parkett. Well over 1000 essays, translated from a variety of languages into German and English, testify to a sustained and dynamic transcontinental exchange. (editorial by publisher)
boek
Keywords: Marclay, Christian; West, Franz; Wearing, Gillian; Sasnal, Wilhelm